Activation of endoplasmic reticulum stress response by enhanced polyamine catabolism is important in the mediation of cisplatin-induced acute kidney injury - Zahedi, Kamyar (PLoS One, 2017)
Cisplatin-induced nephrotoxicity limits its use in many cancer patients. The expression of enzymes involved in polyamine catabolism, spermidine/spermine N(1)-acetyltransferase (SSAT) and spermine oxidase (SMOX) increase in the kidneys of mice treated with cisplatin. We hypothesized that enhanced polyamine catabolism contributes to tissue damage in cisplatin acute kidney injury (AKI). Using gene knockout and chemical inhibitors, the role of polyamine catabolism in cisplatin AKI was examined. Deficiency of SSAT, SMOX or neutralization of the toxic products of polyamine degradation, H(2)O(2) and aminopropanal, significantly diminished the severity of cisplatin AKI. In vitro studies demonstrated that the induction of SSAT and elevated polyamine catabolism in cells increases the phosphorylation of eukaryotic translation initiation factor 2α (eIF2α) and enhances the expression of binding immunoglobulin protein BiP/GRP78) and CCAAT-enhancer-binding protein homologous protein (CHOP/GADD153). The increased expression of these endoplasmic reticulum stress response (ERSR) markers was accompanied by the activation of caspase-3. These results suggest that enhanced polyamine degradation in cisplatin AKI may lead to tubular damage through the induction of ERSR and the consequent onset of apoptosis. In support of the above, we show that the ablation of the SSAT or SMOX gene, as well as the neutralization of polyamine catabolism products modulate the onset of ERSR (e.g. lower BiP and CHOP) and apoptosis (e.g. reduced activated caspase-3). These studies indicate that enhanced polyamine catabolism and its toxic products are important mediators of ERSR and critical to the pathogenesis of cisplatin AKI.